Composite material as well as preparation method and application thereof

By thermal reduction of the precursor of yttrium ruthenate oxide, the heterophase structure of ruthenium element and yttrium oxide is formed, the problem of limited activity in hydrogen evolution catalysis is solved, high-efficiency hydrogen evolution activity and stability is achieved, and the cost of use is reduced.

CN119776903APending Publication Date: 2025-04-08WUYI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937065.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, yttrium ruthenate is limited in hydrogen evolution catalysis because its surface is occupied by A-position inert ions, resulting in the inability to expose the active ruthenium ions, thereby inhibiting the catalytic activity.

Method used

By thermal reduction of the yttrium ruthenate oxide precursor, a heterophase structure of ruthenium element and yttrium oxide is formed. This structure activates more active sites and generates a heterogeneous interface conducive to electron conduction, thereby enhancing the hydrogen evolution activity of the catalyst.

Benefits of technology

The high-efficiency hydrogen evolution activity and stability of yttrium ruthenate catalysts are achieved, reducing the overall cost of catalyst use, and providing a reliable means to prepare high-efficiency catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005211754250000101
    Figure BDA0005211754250000101
  • Figure HDA0005211754260000011
    Figure HDA0005211754260000011
  • Figure HDA0005211754260000021
    Figure HDA0005211754260000021
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method and application thereof, and belongs to the technical field of new energy. The composite material provided by the invention comprises a heterogeneous structure of ruthenium elementary substance and yttrium oxide, and ruthenium elementary substance nanoparticles are loaded on the surface of yttrium oxide. The composite material provided by the embodiment of the invention has the advantages of strong binding force, stable chemical interface, higher catalytic activity and stability and the like when being used for a catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy technology, and in particular to a composite material and a preparation method and application thereof. Background Art

[0002] With the gradual depletion of fossil fuels and the intensification of environmental pollution problems, the search for clean and renewable energy has become a global consensus. Hydrogen, as an efficient, zero-carbon emission energy carrier, is considered an important component of the future energy system. Clean and abundant hydrogen can reduce dependence on fossil fuels, inhibit carbon dioxide emissions, and slow global warming. Electrolysis of water to produce hydrogen uses electricity to decompose water into hydrogen and oxygen. It is a green path to achieve hydrogen production, but its hydrogen evolution reaction (HER) kinetics are slow.

[0003] Although precious metal platinum (Pt) electrocatalysts have high hydrogen evolution activity, their high cost and low reserves hinder their industrial application. Therefore, exploring new hydrogen evolution reaction catalysts that can replace precious metal Pt has become a current technical hotspot and difficulty.

[0004] Although ruthenium (Ru) is a precious metal, it is cheaper than platinum, and its price is only one-twelfth of that of Pt. In practical applications, replacing platinum with ruthenium oxide can reduce costs while maintaining high catalytic activity. Yttrium ruthenate (Y2Ru2O7) is a material with a pyrochlore structure (A2B2O7), which can show better electrochemical catalytic activity and stability than traditional RuO2 in the oxygen evolution reaction (OER) (J.Am.Chem.Soc.2017,139,12076-12083); compared with platinum, yttrium ruthenate can achieve similar or higher catalytic effects with less dosage. The mass fraction of ruthenium in the material is about 41wt.%, which is significantly lower than 76wt.% in RuO2, which helps to further reduce the overall cost of the catalyst. However, since the surface of yttrium ruthenate is preferentially occupied by inert ions at the A position, the surface cannot expose catalytically active ruthenium ions, which seriously inhibits the hydrogen evolution catalytic activity of yttrium ruthenate.

[0005] Therefore, exploring and preparing new composite materials to effectively expose the active ruthenium ions in yttrium ruthenate to enhance its catalytic activity in hydrogen evolution has become an urgent need in current research. Summary of the invention

[0006] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a composite material having excellent hydrogen evolution catalytic activity and catalytic stability.

[0007] The invention also provides a method for preparing the composite material.

[0008] The invention also provides a hydrogen evolution catalyst.

[0009] The invention also provides a cathode for hydrogen evolution by electrolyzing water.

[0010] The invention also provides application of the composite material.

[0011] According to an embodiment of the first aspect of the present invention, there is provided a composite material comprising a heterogeneous structure of ruthenium and yttrium oxide, wherein ruthenium nanoparticles are loaded on the surface of yttrium oxide.

[0012] The composite material provided according to the embodiment of the present invention has at least the following beneficial effects:

[0013] The composite material provided in the embodiment of the present invention has ruthenium nanoparticles loaded on the surface of yttrium oxide (Y2O3), and has a heterogeneous structure of ruthenium and yttrium oxide. When used as a catalyst, it has the advantages of strong binding force, stable chemical interface, higher catalytic activity and stability.

[0014] The heterogeneous structure provided by the embodiment of the present invention can not only activate a large number of active sites but also produce a heterogeneous interface that is conducive to electronic conduction. Due to the similarity between Ru metal crystals and Y2O3 materials and the catalytic synergy between Y2O3 and three-dimensional Ru metal, the ruthenium metal supported by the heterogeneous catalyst exhibits significant hydrogen evolution activity. The principle is to utilize the different adsorption capacities of hydrogen between the components to transfer hydrogen from the hydrogen-rich phase to the hydrogen-poor phase, and work together to enhance the hydrogen evolution activity on the catalyst surface.

[0015] According to some embodiments of the present invention, the composite material includes optional yttrium ruthenate oxide. In some embodiments, the composite material exists in the form of three mixed phases of Y2Ru2O7, Ru and Y2O3.

[0016] According to some preferred embodiments of the present invention, the composite material is composed of only two phases of ruthenium and yttrium oxide. The coexistence of the two phases forms a large number of heterogeneous interfaces, which are conducive to the generation of synergistic electronic effects and enhance catalytic activity; at the same time, the solid two-phase structure enables Ru nanoparticles to be firmly anchored on the Y2O3 matrix, preventing them from falling off or dissolving during long-term electrolysis, thereby enhancing catalytic stability.

[0017] According to some embodiments of the present invention, the particle size of the ruthenium element is 2-3 nm, for example, about 2.5 nm.

[0018] According to some embodiments of the present invention, the particle size of yttrium oxide is 4-5 nm; for example, about 4.5 nm.

[0019] According to some embodiments of the present invention, the particle size of the composite material is 5-6 nm; for example, about 5.5 nm.

[0020] According to an embodiment of the second aspect of the present invention, there is provided a method for preparing the composite material, comprising the following steps:

[0021] S1. Providing and / or preparing a precursor yttrium ruthenate;

[0022] S2. Thermally reducing the precursor.

[0023] The preparation method according to the embodiment of the present invention has at least the following beneficial effects:

[0024] The embodiment of the present invention thermally reduces the Y2Ru2O7 oxide precursor to segregate the nano-metal Ru, while the pyrochlore structure of Y2Ru2O7 is disintegrated, causing the structure to change, thereby obtaining a composite material with a heterogeneous structure including Ru element and yttrium oxide, thereby obtaining a composite material with more active sites exposed, providing a reliable means for exploring the preparation of high-efficiency catalysts.

[0025] According to the embodiments of the present invention, the composite material prepared by the method of the present invention has excellent hydrogen evolution catalytic activity and catalytic stability.

[0026] In summary, the method of the embodiment of the present invention has simple raw materials, easy process flow, suitable for large-scale preparation, green and safe reaction process, no other toxic additives, and the composite catalyst with heterogeneous structure prepared by the method has the advantages of strong binding force, stable chemical interface, higher catalytic activity and stability, etc. The present invention has important scientific significance and application value for exploring the design and preparation of multi-component catalytic systems and their applications.

[0027] In some preferred embodiments of the present invention, the prepared composite material also includes unreacted Y2Ru2O7 oxide phase.

[0028] According to some embodiments of the present invention, compared with the precursor yttrium ruthenate, the composite material has a rough surface from an originally smooth surface, and the atomic arrangement in the lattice becomes more disordered, which also proves the formation of the heterogeneous phase structure.

[0029] According to some embodiments of the present invention, in step S1, the precursor can be purchased commercially. Alternatively, the preparation method of the precursor includes at least one of a sol-gel method, a solid phase synthesis method or a co-precipitation method.

[0030] According to some embodiments of the present invention, in step S1, the precursor is prepared by a sol-gel method. The sol-gel method can achieve uniform mixing of various components through a liquid precursor solution, and can synthesize highly uniform materials; and can synthesize materials at a relatively low temperature without high-temperature sintering.

[0031] According to some embodiments of the present invention, in step S1, the preparation of the precursor comprises the following steps:

[0032] S1a. The Y salt, Ru salt and complexing agent are mixed in water, reacted and dried;

[0033] S1b. calcining the solid product obtained in step S1a in an oxygen-containing atmosphere.

[0034] According to some embodiments of the present invention, in step S1a, the complexing agent includes citric acid and / or ethylenediaminetetraacetic acid.

[0035] According to some embodiments of the present invention, in step S1a, the Y salt includes at least one of yttrium nitrate, yttrium nitrate hydrate, yttrium trichloride and yttrium trichloride hydrate.

[0036] According to some embodiments of the present invention, in step S1a, the Ru salt includes at least one of ruthenium chloride, ruthenium chloride hydrate and ruthenium nitrosyl nitrate.

[0037] According to some embodiments of the present invention, in step S1a, the molar volume ratio of the complexing agent to water is 3.2 mmol:30 mL to 3.2 mmol:40 mL, for example, about 3.2 mmol:35 mL.

[0038] According to some embodiments of the present invention, in step S1a, the molar ratio of Y, Ru and the complex in the Y salt and Ru salt is 1:0.95:2 to 1:1.05:4, for example, about 1:0.92:2, about 1:1:3 or about 1:1.02:4, preferably 1:1:2 to 1:1:4.

[0039] According to some embodiments of the present invention, step S1a further comprises adding an acid solution to the mixed reaction, wherein the acid solution comprises concentrated nitric acid: usually a 68-70% nitric acid aqueous solution, thereby avoiding the hydrolysis and precipitation of the Y salt and the Ru salt.

[0040] According to some embodiments of the present invention, in step S1a, the volume ratio of the acid solution to water is 1:30 to 1:40, for example, about 1:35.

[0041] According to some embodiments of the present invention, in step S1a, the reaction is a water bath reaction.

[0042] According to some embodiments of the present invention, in step S1a, the reaction temperature is 80-100°C, for example, about 85°C, about 90°C or about 95°C.

[0043] According to some embodiments of the present invention, in step S1a, the reaction time is 4 to 6 hours, for example about 5 hours.

[0044] According to some embodiments of the present invention, in step S1a, the reaction is carried out under stirring to accelerate the formation of gel.

[0045] According to some embodiments of the present invention, in step S1a, the drying temperature is 120-160°C, for example, about 130°C, about 140°C or about 150°C.

[0046] According to some embodiments of the present invention, in step S1a, the drying time is 6 to 10 hours, for example, about 7 hours, 8 hours or about 9 hours.

[0047] According to some embodiments of the present invention, in step S1b, the oxygen-containing atmosphere includes at least one of air and oxygen.

[0048] According to some embodiments of the present invention, in step S1b, the calcination includes a first constant temperature stage and a second constant temperature stage which are performed sequentially.

[0049] According to some embodiments of the present invention, the temperature of the first constant temperature stage is 600-800° C. For example, it may be about 650° C., 700° C. or 750° C.

[0050] According to some embodiments of the present invention, the duration of the first constant temperature stage is 6 to 8 hours, for example, specifically about 7 hours.

[0051] According to some embodiments of the present invention, the temperature of the second constant temperature stage is 1000-1100° C. For example, it may be about 1050° C.

[0052] According to some embodiments of the present invention, the duration of the second constant temperature stage is 10 to 12 hours, for example, specifically about 11 hours.

[0053] According to some embodiments of the present invention, in step S1b, the heating rates of the first constant temperature stage calcination and the second constant temperature stage are independently 3-10°C / min, for example, about 5°C / min or about 8°C / min.

[0054] According to some embodiments of the present invention, step S1b further includes a step of cooling after the calcination.

[0055] According to some embodiments of the present invention, in step S2, the thermal reduction atmosphere includes a reducing gas, specifically hydrogen and / or ammonia.

[0056] According to some embodiments of the present invention, in step S2, the thermal reduction atmosphere is a mixed atmosphere further comprising argon, wherein the volume percentage of the reducing gas is 3-8%, for example, about 5%, such as 5% H2 / Ar or 5% NH3 / Ar.

[0057] According to some embodiments of the present invention, in step S2, the gas flow rate of the thermal reduction is 150-250 sccm, for example, about 200 sccm.

[0058] According to some embodiments of the present invention, in step S2, the temperature of the thermal reduction is 350-650°C, preferably 400-600°C, and more preferably 400-500°C. For example, it can be about 360°C, about 370°C, about 380°C, about 390°C, about 410°C, about 420°C, about 430°C, about 440°C, about 450°C, about 460°C, about 470°C, about 480°C, about 500°C or about 550°C.

[0059] According to some embodiments of the present invention, in step S2, the thermal reduction time is 2 to 10 hours, preferably 3 to 9 hours, for example, about 4 hours, about 5 hours, about 6 hours, about 7 hours or about 8 hours.

[0060] According to some embodiments of the present invention, in step S2, the heating rate of the thermal reduction is 3-10°C / min, for example, about 5°C / min or about 8°C / min.

[0061] According to some embodiments of the present invention, the Ru content in the pore-controlling oxide precursor Y2Ru2O7 is adjusted by adjusting the thermal reduction conditions such as temperature and time. 4+ The degree of reduction and phase change in the lattice, and then the distribution of metal Ru and the electronic structure of the catalyst are controlled to obtain a high-performance electrochemical hydrogen evolution reaction catalyst with multiple active components. The composite material with Ru-Y2O3 heterogeneous structure prepared by the method of the embodiment of the present invention has the advantages of strong bonding, stable chemical interface, higher catalytic activity and stability, etc.

[0062] In short, the embodiments of the present invention obtain a composite material with more exposed active sites by reducing the precursor oxide Y2Ru2O7 to different degrees, providing a reliable means for exploring the preparation of efficient catalysts.

[0063] According to some preferred embodiments of the present invention, when the thermal reduction temperature reaches a certain temperature, for example, above 400°C, the Ru element precipitates from the octahedral site, and the crystal structure of the Y2Ru2O7 pyrochlore is completely disintegrated, thereby obtaining a two-phase structure composite material of Y2O3 anchoring the Ru element. The composite material has particularly excellent hydrogen evolution reaction (HER) activity and stability, which is mainly attributed to the generation of active site Ru, and the synergistic effect between Y2O3 and Ru improves the HER performance.

[0064] According to some embodiments of the present invention, step S2 further includes a step of cooling after the thermal reduction.

[0065] According to an embodiment of the third aspect of the present invention, a hydrogen evolution catalyst is provided, wherein the raw material for preparing the hydrogen evolution catalyst comprises the composite material or the composite material prepared by the preparation method, and the hydrogen evolution catalyst has excellent hydrogen evolution catalytic activity and catalytic stability.

[0066] According to some embodiments of the present invention, the hydrogen evolution catalyst may be the composite material itself, or a mixture of the composite material and an auxiliary agent, wherein the auxiliary agent includes at least one of a conductive agent and a binder.

[0067] According to some embodiments of the present invention, the hydrogen evolution catalyst also has alkaline oxygen evolution catalytic activity, so it can be used alone as a hydrogen evolution catalyst in water electrolysis, or as a bifunctional catalyst.

[0068] According to an embodiment of the fourth aspect of the present invention, there is provided a water electrolysis hydrogen evolution cathode, which comprises the above-mentioned hydrogen evolution catalyst.

[0069] According to an embodiment of the fifth aspect of the present invention, there is provided a use of the hydrogen evolution catalyst in water electrolysis.

[0070] Since the application adopts all the technical solutions of the hydrogen evolution catalyst of the above embodiment, it at least has all the beneficial effects brought by the technical solutions of the above embodiment.

[0071] The composite material and the preparation method thereof provided in the embodiments of the present invention have important scientific significance and application value for exploring the design and preparation of a multi-component catalytic system and its application.

[0072] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0074] Figure 1 It is the XRD spectrum of the composite material prepared by Examples 1 to 3 of the present invention and Comparative Example 1;

[0075] Figure 2 It is the XRD spectrum of the composite material prepared by Example 1, Example 4 and Comparative Examples 2-3 of the present invention;

[0076] Figure 3 is a transmission electron microscope (HRTEM) image of the ruthenium-yttrium oxide composite material prepared in Example 1 of the present invention;

[0077] Figure 4 are polarization curves of the composite materials prepared in Examples 1 to 3 of the present invention and Comparative Example 1 and a commercial carbon-supported platinum catalyst;

[0078] Figure 5 are polarization curves of the composite materials prepared in Examples 1 and 4 of the present invention and Comparative Examples 2 to 3;

[0079] Figure 6 1 is the stability curve of the composite material prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0080] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.

[0081] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0082] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0083] Unless otherwise indicated herein, recitation of ranges of values ​​herein is merely intended to serve as a shorthand method of referring individually to each separate value falling within the range, and each separate value is incorporated into the specification as if it were individually recited herein. Unless otherwise indicated herein, all exact values ​​provided herein represent corresponding approximate values ​​(e.g., all exact exemplary values ​​provided with respect to a particular factor or measurement can be considered to also provide corresponding approximate measurements, modified by "about" where appropriate).

[0084] As used herein, when used in connection with a numerical value, the term "about" is intended to include a set or range of numerical values. For example, "about" means a numerical range of ±5%, ±2%, ±1%, ±0.5%, ±0.2%, or ±0.1% of the numerical value. In one embodiment, the term "about" refers to a numerical range of 5% more or less than a particular value. In another embodiment, the term "about" refers to a numerical range of 2% more or less than a particular value. In another embodiment, the term "about" refers to a numerical range of 1% more or less than a particular value.

[0085] Example 1

[0086] This embodiment prepares a ruthenium-yttrium oxide composite material, and the specific steps are as follows:

[0087] S1. Dissolve yttrium nitrate (Y(NO3)3·6H2O, 0.8mmol), ruthenium chloride (RuCl3, 0.8mmol) and citric acid (3.2mmol) in stoichiometric ratio in 30mL of deionized water, drop 1mL of nitric acid solution (concentration 68-70%, i.e. directly use commercially available concentrated nitric acid), and mix well. Place the obtained mixed solution in a water bath, set the water bath temperature to 80℃ and heat it with continuous magnetic stirring for 5h; place the obtained gel in a drying oven, set the constant temperature at 120℃ for 6h, and obtain dry powder.

[0088] S2. The dried powder was transferred to a corundum crucible and placed in a muffle furnace for heating (air atmosphere), and the temperature was raised from room temperature to 600°C at a heating rate of 5°C / min, and the temperature was kept constant for 6 hours; then the temperature was raised to 1000°C at a heating rate of 5°C / min, and the temperature was kept constant for 12 hours. After the program was completed and the muffle furnace was cooled to room temperature, the precursor Y2Ru2O7 material was obtained.

[0089] S3. The obtained Y2Ru2O7 material is placed in a tube furnace, and a 5% H2 / Ar mixed gas is introduced into the tube furnace at a flow rate of 200 sccm. The tube furnace is ventilated for 1 hour before heating to remove the air in the tube furnace. Then, the tube furnace is heated from room temperature to 450°C at a heating rate of 5°C / min, kept at a constant temperature for 6 hours, and then naturally cooled to room temperature to obtain a ruthenium-yttrium oxide composite material.

[0090] Example 2

[0091] This embodiment prepares a ruthenium-yttrium oxide composite material, which differs from Embodiment 1 only in that in step S3, the constant temperature time of hydrogen thermal reduction is 9 hours.

[0092] Example 3

[0093] This embodiment prepares a ruthenium-yttrium oxide composite material, which differs from Embodiment 1 only in that in step S3, the constant temperature time of hydrogen thermal reduction is 3 hours.

[0094] Example 4

[0095] This embodiment prepares a ruthenium-yttrium oxide composite material, which is different from the embodiment 1 only in that in step S3, the constant temperature of hydrogen thermal reduction is 600°C.

[0096] Comparative Example 1

[0097] This comparative example prepares a composite material, which differs from Example 1 only in that the hydrogen thermal reduction step S3 is not included.

[0098] Comparative Example 2

[0099] This comparative example prepares a composite material, which is different from Example 1 only in that in step S3, the constant temperature of hydrogen thermal reduction is 300°C.

[0100] Comparative Example 3

[0101] This comparative example prepares a composite material, which differs from Example 1 only in that in step S3, the constant temperature of hydrogen thermal reduction is 750°C.

[0102] Test Case

[0103] This test example characterizes and tests the morphology, structure and performance of the composite materials obtained in the above embodiments and comparative examples.

[0104] 1) Morphological and structural characterization

[0105] Figure 1The XRD patterns of the composite materials prepared by Examples 1 to 3 after thermal reduction treatment for different times and Comparative Example 1 without thermal reduction treatment are shown. The results show that the diffraction peaks of the composite materials prepared by the embodiments of the present invention can correspond well to the standard cards of ruthenium metal (PDF#88-1734) and the standard cards of yttrium oxide (PDF#79-1256), and no characteristic peaks of yttrium ruthenate are shown; while the diffraction peaks of the composite materials prepared by Comparative Example 1 can correspond well to the standard PDF card of yttrium ruthenate (PDF 83-0637). This shows that the embodiments of the present invention successfully transform the physical phase of yttrium ruthenate into the physical phase of yttrium oxide and ruthenium element through the hydrogen thermal reduction step, forming a ruthenium-yttrium oxide composite material with a heterogeneous structure. This heterogeneous structure has the following advantages: 1. It can regulate the interface and interaction between materials, improve the electronic structure and charge transfer characteristics, and thus improve the efficiency of the catalytic reaction; 2. Ruthenium metal nanoparticles loaded on the surface of yttrium oxide can enhance the electrical conductivity of the catalyst and increase the rate of the catalytic reaction.

[0106] Figure 2 The XRD patterns of the composite materials prepared by Examples 1 and 4 and Comparative Examples 2-3 subjected to thermal reduction treatment at different temperatures are shown. The results show that when the reduction temperature is 300°C, the composite material obtained by annealing in Comparative Example 2 still has the diffraction peak of yttrium ruthenate; when the thermal reduction temperature is 450°C, 600°C, and 750°C, the composite materials prepared by Example 1 (450°C), Example 4 (600°C), and Comparative Example 3 (750°C) can observe two new diffraction peaks that are obviously different from yttrium ruthenate, and the two new diffraction peaks belong to the characteristic peaks of Y2O3 (PDF#79-1256) and ruthenium metal (PDF#88-1734), respectively. This shows that when yttrium ruthenate is reduced with hydrogen at 300°C, there is no obvious crystal orientation change in yttrium ruthenate and no phase transformation occurs; however, when the temperature continues to rise, yttrium ruthenate undergoes a phase change, a new phase is generated, and a ruthenium-yttrium oxide heterogeneous structure composite material is further prepared.

[0107] Figure 3 The transmission electron microscope image of the ruthenium-yttrium oxide composite material prepared in Example 1 is shown. The results show that the ruthenium single substance is precipitated from the octahedral site, the crystal structure of the pyrochlore is completely disintegrated, and the ruthenium single substance nanoparticles are loaded on Y2O3 to form a heterogeneous structure of ruthenium single substance and yttrium oxide. Among them, the HRTEM shows a diffraction stripe with a lattice spacing of 0.206nm, which belongs to the (101) crystal plane of the ruthenium single substance. The HRTEM also shows a diffraction stripe with a lattice spacing of 0.303nm, which belongs to the (222) crystal plane of yttrium oxide.

[0108] 2) Electrochemical hydrogen evolution performance test

[0109] Preparation of working electrode: 5 mg of catalyst (product of the embodiment and comparative example, and commercial 20 wt.% Pt / C catalyst (purchased from Johnson Matthey Chemical Co., Ltd.) and 1 mg of carbon black were dispersed in a mixed solution of 0.8 mL of water, 0.17 mL of isopropanol and 0.03 mL of 5 wt.% Nafion. After ultrasonic homogenization, 10 uL of the suspension was transferred and dropped on the polished glassy carbon electrode surface, and then dried naturally for use.

[0110] Hydrogen evolution performance test: The above-prepared electrode was used as the working electrode, mercury oxide electrode (Hg / HgO) as the reference electrode, carbon rod as the counter electrode, and 1M KOH aqueous solution as the electrolyte. The hydrogen evolution performance was tested on an electrochemical workstation. The hydrogen evolution catalytic performance was evaluated by polarization curve test. By applying 10 mA cm -2 The working current density is used to measure the change of electrode voltage over time (more than 10 h), that is, the electrochemical hydrogen evolution stability of the catalyst is evaluated through the chronopotentiometry curve.

[0111] Figure 4 The effect of different thermal reduction treatment times on the hydrogen evolution performance of yttrium ruthenate (YRO) oxide is shown. Figure 4 As shown, Examples 1 to 3, Comparative Example 1 and Pt / C catalysts at 10 mA cm -2 The corresponding hydrogen evolution overpotentials are 70mV, 128mV, 142mV, 168mV and 34mV, respectively. It can be seen that when the ruthenium-yttrium oxide composite material prepared in the embodiment of the present invention is used for hydrogen evolution catalysis, its catalytic activity is much higher than that of the precursor yttrium ruthenate material of Comparative Example 1, which is due to the heterogeneous structure formed by ruthenium element and yttrium oxide. Moreover, compared with Examples 2 to 3 and Comparative Example 1, Example 1 shows better catalytic performance in hydrogen evolution reaction, indicating that the reduction time is crucial for improving the active sites of the catalyst and thus improving the HER performance. Under optimal reduction conditions, certain atoms or groups on the catalyst surface are reduced to a state that is more conducive to hydrogen adsorption and dissociation. On the contrary, insufficient or excessive reduction time may cause the active sites to fail to reach the optimal state, thereby reducing the HER performance.

[0112] Figure 5 The effect of different thermal reduction temperatures on the hydrogen evolution performance of yttrium ruthenate oxide is shown. Figure 5 As shown, Examples 1, 4 and Comparative Examples 2-3 at 10 mA cm -2The corresponding hydrogen evolution overpotentials are 70mV, 114mV, 161mV and 210mV, respectively. It can be seen that the ruthenium-yttrium oxide composite material prepared within the reduction temperature range of the present invention has higher hydrogen evolution catalytic activity and exhibits better hydrogen evolution reaction catalytic activity. Moreover, compared with Example 4 and Comparative Examples 2 to 3, Example 1 exhibits better hydrogen evolution reaction catalytic performance, indicating that the reduction temperature is crucial for improving the active sites of the catalyst and thus improving the HER performance. The composite material prepared in Example 1 contains uniformly dispersed Ru nanoparticles, which optimizes the exposure of catalytic active sites. In contrast, Comparative Example 2 performed poorly due to insufficient Ru separation caused by the low reduction temperature, while Comparative Example 3 used an excessively high thermal reduction temperature, which caused excessive reduction and aggregation of Ru particles, resulting in a decrease in the availability of active sites, thereby inhibiting HER performance.

[0113] In order to investigate the stability of the ruthenium-yttrium oxide composite material prepared by the present invention, Figure 6 As shown, the composite materials prepared in Example 1 and Comparative Example 1 were subjected to a constant current density of 10 mA cm -2 The durability of the electrocatalyst was evaluated by chronopotentiometry at a current density of . As can be seen from the figure, after 60 hours of durability testing, the overpotential of the Ru-Y2O3 composite material prepared in Example 1 has hardly changed. However, the catalytic performance of the Y2Ru2O7 material prepared in Comparative Example 1 is severely attenuated after continuous electrolysis. This shows that the Ru-Y2O3 heterogeneous structure composite material prepared by thermal reduction reaction of the present invention has strong bonding force and stable chemical interface, thereby showing significantly improved stability.

[0114] The results of the composite materials of the above-mentioned embodiments and comparative examples are summarized in the following Tables 1 and 2.

[0115] Table 1 Overpotential data of the composite materials prepared in the examples and comparative examples (test conditions 10 mA cm -2 ).

[0116] Overpotential mV Example 1 70 Example 2 128 Example 3 142 Example 4 114 Comparative Example 1 168 Comparative Example 2 161 Comparative Example 3 210 Pt / C Catalyst 34

[0117] Table 2 Relevant properties of the composite materials prepared in Example 1 and Comparative Example 2

[0118]

[0119] The embodiment of the present invention firstly adopts the sol-gel method to prepare Y2Ru2O7 (YRO) of pyrochlore structure; and by regulating the thermal reduction conditions, including temperature and time, a series of composite materials with different composition structures are prepared, and the structure-activity relationship between the structural change of pyrochlore and HER performance is explored. The results show that by thermally reducing the precursor Y2Ru2O7 to different degrees, a composite material with more active sites exposed can be obtained, which provides a reliable means for exploring the preparation of efficient catalysts. In particular, when the thermal reduction temperature reaches a certain temperature (for example, above 400°C), Ru single substance precipitates from the octahedral site, and the crystal structure of pyrochlore is completely disintegrated, and a ruthenium-yttrium oxide heterogeneous structure composite material with Y2O3 anchoring Ru single substance is obtained. The composite material has particularly excellent HER activity, which is mainly attributed to the generation of active site Ru, and the synergistic effect between Y2O3 and Ru improves the HER performance.

[0120] In summary, the composite material provided by the present invention has high catalytic activity and catalytic stability when used as a hydrogen evolution catalyst. The preparation method provided by the present invention has simple raw materials, is easy to operate, and is suitable for large-scale preparation. The prepared composite material catalyst has the advantages of strong binding force, stable chemical interface, higher catalytic activity and stability. The present invention has important scientific significance and application value for exploring the design and preparation of multi-component catalytic systems and their applications.

[0121] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A composite material, characterized in that: The invention comprises a heterogeneous structure of ruthenium and yttrium oxide, wherein ruthenium nanoparticles are loaded on the surface of yttrium oxide.

2. The composite material according to claim 1, characterized in that The particle size of the ruthenium single substance is 2 to 3 nm; and / or the particle size of the yttrium oxide is 4 to 5 nm; and / or the particle size of the composite material is 5 to 6 nm.

3. The method for preparing the composite material according to claim 1 or 2, characterized in that: The following steps are involved: S1. Providing and / or preparing a precursor yttrium ruthenate; S2. Thermally reducing the precursor.

4. The preparation method according to claim 3, characterized in that: In step S1, the preparation method of the precursor includes at least one of a sol-gel method, a solid phase synthesis method or a co-precipitation method.

5. The preparation method according to claim 3, characterized in that: In step S1, the precursor is prepared by a sol-gel method, which includes the following steps: S1a. The Y salt, Ru salt and complexing agent are mixed in water, reacted and dried; S1b calcining the solid product obtained in step S1a in an oxygen-containing atmosphere; in: The complexing agent includes citric acid and / or ethylenediaminetetraacetic acid; And / or, the Y salt comprises at least one of yttrium nitrate, yttrium nitrate hydrate, yttrium trichloride and yttrium trichloride hydrate; and / or, the Ru salt comprises at least one of ruthenium chloride, ruthenium chloride hydrate and ruthenium nitrosyl nitrate; And / or, the molar ratio of Y, Ru in the Y salt and Ru salt to the complexing agent is 1:0.95:2 to 1:1.05:

4.

6. The preparation method according to claim 5, characterized in that: In step S1a: The reaction is a water bath reaction; And / or, the reaction temperature is 80-100°C; the reaction time is 4-6h; And / or, the drying temperature is 120-160° C.; the drying time is 6-10 hours; And / or, in step S1b: The calcination comprises a first constant temperature stage and a second constant temperature stage which are carried out sequentially; The temperature of the first constant temperature stage is 600-800° C.; the time of the first constant temperature stage is 6-8 hours; And / or, the temperature of the second constant temperature stage is 1000-1100° C.; the time of the first constant temperature stage is 10-12 hours.

7. The preparation method according to any one of claims 3 to 6, characterized in that In step S2: The thermal reduction atmosphere includes hydrogen and / or ammonia; preferably, the thermal reduction atmosphere is a mixed atmosphere further including argon; And / or, the temperature of the thermal reduction is 350-650°C; preferably 400-600°C; And / or, the thermal reduction time is 2 to 10 hours; preferably 3 to 9 hours.

8. A hydrogen evolution catalyst, characterized in that The raw material for preparing the hydrogen evolution catalyst comprises the composite material according to claims 1 to 2 or the composite material prepared by the preparation method according to any one of claims 3 to 7.

9. A cathode for hydrogen evolution by water electrolysis, characterized in that: Comprising the hydrogen evolution catalyst according to claim 8.

10. Use of the hydrogen evolution catalyst as claimed in claim 8 in electrolysis of water.